PENGARUH AROMATERAPI BUNGA MAWAR TERHADAP PENURUNAN INTENSITAS NYERI PADA PASIEN POST SECTIO CAESAREA DI RSUD TANJUNG PURA - Meliala, Jusup; Susana, Sarka Ade; Palestine, Bondan (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2023)
Postoperative cesarean problems due to incision tears in the abdominal wall and uterine wall tissue can cause changes in continuity which cause pain in the surgical scars. Mild post-cesarean section pain occurs in 15% of cases, moderate pain in 35% of cases, severe pain in 30% of cases, and extreme pain in 20% of cases. Provision of rose aromatherapy is thought to reduce postoperative pain of sectio caesarea. To determine the effect of rose aromatherapy on postoperative pain of sectio caesarea with spinal anesthesia. This research is a quasi-experimental study using the Non-equivalent Control Group Design. This research was conducted at the Tanjung Pura Regional General Hospital, in March-April 2023. The population for this research study was cesarean section mothers at Tanjung Pura Hospital, totaling 40 people. Samples were obtained as many as 36 people. Data analysis was performed univariately in the frequency distribution table and bivariate analysis using the Mann Whitney test because the data were not normally distributed. The intensity of pain in the intervention group with rose aromatherapy, namely cesarean section mothers after spinal anesthesia at the Tanjung Pura Regional General Hospital before treatment (pretest) the majority of moderate pain (61.1%) or scale 6, and posttest all mild pain (100.0 %) or scale 1. The majority of pain intensity in the control group (pretest) is severe pain (55.6%) or scale 7, and posttest the majority of moderate pain (55.6%) or scale 4. There is an effect of giving rose aromatherapy to postoperative pain sectio caesarea with spinal anesthesia at Tanjung Pura Regional General Hospital, p = 0.000 <0.05. The mean (mean) pain intensity in the intervention group was 1.89, lower than the pain intensity in the intervention group, 3.56. There is an effect of giving rose aromatherapy to postoperative sectio caesarea pain with spinal anesthesia.